Turkish Adaptation of Healthy Habits Questionnaire for Adolescents: Diet, Physical Activity, Screen Time, and Sleep Habits - ERGÜN, AYŞE (My University, 2024)
Objective: The main purpose of this study was to adapt the adolescent Healthy Habits Questionnaire (HHQ) to the Turkish language and to test its validity and reliability. The study was also examined the diet, physical activity, screen time, and sleep habits of adolescents. Methods: This study is a methodological and descriptive design. The sample of the research consists of 320 students. The validity of the HHQ was evaluated by the content validity index, the reliability by test-retest correlations, and the kappa coefficient of agreement. Number and percentage values were used for descriptive features. Results: The content validity index of HHQ was found to be 0.96. The test-retest correlations of questions containing continuous variables were found to be between 0.44 and 0.91. Kappa values of questions containing categorical variables were between 0.7 and 0.94. It was found that 91.8% of the adolescents consumed less than three servings of vegetables, 76.9% of them consumed less than 2 servings of fruit, and 80.5% of them consumed less than 2 glasses of milk. In addition, it was determined 40.2% of the adolescents used screen use more than two hours, 47.6% did less than one hour of physical activity and 30.2% slept less than eight hours. Conclusion: HHQ was found as a valid and reliable measurement tool. It was determined that the adolescents did not consume enough vegetables, fruits, water, and milk and did not engage in sufficient physical activity. Keywords: Adolescence, fruit, screen time, sleeping, vegetable.
Keywords: Hemşirelik; Halk Sağlığı Hemşireliği; Sağlık Bilimleri; Nursing; Public Health Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing; Adolescence; fruit; screen time; sleeping; vegetabl